Dynamics of Public Policy on Economic Activity: The Case of Pakistan - Saima Shafique (IDEA PUBLISHERS, 2020)
The unanticipated domestic and international changes in conjunction with policy discretion become reason for shocks to overall economy that affect overall economic growth. Based on methodology by Blanchard and Perotti (2002) the study used timing of fiscal decisions in a Structural Vector Auto-Regression (SVAR) to map dynamics of shocks due to tax revenue, government expenditures and aggregate output in Pakistan. When tax decisions precede expenditure decision, the tax shocks have a volatile short run impact causing expenditures to sharply adjust. Expenditure shocks persistently increase tax revenues and government expenditures. But in the second specification, expenditure shocks reduce the tax revenue and aggregate output that reverts to equilibrium only in the long run. The response of output shocks is almost identical for both the scenarios. Therefore, growth in output increases taxes collection in Pakistan enabling better management of burden of debt and deficit.